Propriedades de medição da escala de advocacia do paciente para enfermeiros de terapia intensiva - Menezes, Jennifer Aguilar Leocadio de (2022)
The organizational structure of the Intensive Care Unit (ICU), as well as the clinical and ethical issues involved in the care of patients admitted to it, confront the professional nurse with situations that require the exercise of patient advocacy. In order for them to play the role of defender, some factors will influence, among them: their beliefs and attitudes, as well as certain barriers inherent to professional practice in this sector. Objectives: To validate the Patient Advocacy Scale by Intensive Care Nurses (EAPEnf-ICU); Characterize nurses according to sociodemographic and work variables; To analyze beliefs and actions of intensive care nurses in the practice of patient advocacy. Methodology: This is a methodological study, with a cross-sectional design, carried out with 377 intensive care nurses working in adult intensive care units, both from the Unified Health System (SUS) and from private institutions, with representation from the 26 Brazilian states and the Federal District. In the selection of participants, the non-probabilistic convenience sampling method was used, so that the informants were selected according to their availability. Participants were recruited through e-mails addressed to professionals, heads of institutional services, researchers and professors from different cities in the country, requesting that the access link to the instrument be disseminated in their networks of professional contacts, as well as through social networks. Data collection took place from January to June 2021, through an online form (Google forms). The data were organized in a table in the Excel 2010® program and, later, were submitted to statistical tests to ensure the measure's construct validity. The project was submitted to the Ethics Committee in Research with Human Beings via Plataforma Brasil and approved according to CAEE 84197418.8.0000.0121. Results: The results showed that the sample and the data correlation matrix were adequate for this analysis: KMO = 0.88; Bartlett's sphericity test, χ² (1596) = 10,992.5, p < 0.001. From the structural exploration of the scale, through Exploratory Factor Analysis (AFE) and Confirmatory Factor Analysis (CFA), as well as the analysis of the internal consistency of the measure, the final version of the EAPEnf-UTI was composed of 54 items, distributed in 5 dimensions/factors: Factor 1 – Clinical and organizational advocacy in intensive care; Factor 2 – Barriers associated with the clinical and organizational complexity of intensive care; Factor 3 – Attitudes to promote the autonomy of patients and family members in intensive care; Factor 4 – Barriers associated with ethical-professional divergences and limits in intensive care; and Factor 5 – Personal and professional background of the intensive care nurse. The scale's internal consistency indexes considering each factor were: Factor 1 (α = 0.97, = 0.98); Factor 2 (α = 0.91,  = 0.94); Factor 3 (α = 0.90,  = 0.94); Factor 4 (α = 0.89,  = 0.94); Factor 5 (α = 0.83,  = 0.89). Conclusions: The final version of the EAPEnf-ICU consisted of 54 items, divided into 5 factors, and constitutes a valid, reliable and reliable instrument to assess the beliefs and actions of intensive care nurses in the exercise of patient advocacy.